The Productivity Gap in Latin America: Lessons from 50 Years of Development - Eduardo Fernández Arias; Sergio Rodríguez-Apolinar (Inter-American Development Bank (IDB), 2016)
This paper combines development accounting exercises with economic theory to assess the importance of total factor productivity and the accumulation of factors of production as engines of growth in Latin America. Using the new, drastically revised Penn World Table (PWT) and Barro-Lee datasets, the paper shows that lower and non-convergent income relative to successful development benchmarks are explained by subpar productivity gains rather than slower factor accumulation. The empirical analysis of the interplay between productivity and accumulation in the process of development suggests that one explanation for this pattern is that investment in Latin America is not as productivity-enhancing as in less distorted economies.
hdl:11319/7613
Keywords: O11; O47; 330; Economic growth; Total factor productivity; Development; Productive development policies